Perancangan User Experience pada Aplikasi Pencarian Orang Hilang menggunakan Metode Human Centered Design - Charles Sanggalangi; Fais Al Huda; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
A missing person is someone whose whereabouts are unknown. Approximately 75% of missing person cases will be resolved within approximately 48 hours after the missing person report is made. However, many cases of missing persons that occur more than 48 hours and the longer the person is missing, the likelihood of their survival decreases. This study aims to design the user experience for a missing person search application using the Human Centered Design (HCD) method and cognitive walkthrough testing. The HCD method is used to ensure that the application is easy to use for the user and meets the user's needs. Meanwhile, cognitive walkthrough testing is carried out to test whether the application can be understood and operated correctly by the user. The result of this study is a user experience design that meets the user's needs and can be easily understood by the user. The results of the cognitive walkthrough testing showed that respondents successfully completed all the given testing scenarios, but there were also errors that occurred during the testing process